Functional outcome and patient satisfaction with a 'self- care' protocol for minimally displaced distal radius fractures. (September 2022) - Hutchison, A- M.; Bodger, O.; Whelan, R.; Russell, I. D.; Man, W.; Williams, P.; Bebbington, A.
No abstract available